Numerical Studies of Thermo Acoustic Prime Mover on the Application of Renewable Energy - Jaanaki, S. M.; Krishna Moorthy, V.; Praveen, Uma (Asian Journal of Electrical Sciences, 2019)
Thermo acoustic Prime Movers (TAPMs) work on the principle of conversion of heat energy to sound energy which is used to drive engine by the variation of pressure created by acoustic power. In order to develop a system theoretical knowledge about the dimension of a prime mover, working gas and operating temperature are required. This paper presents the studies of influence of working fluid in Thermoacoustic Prime mover using Delta EC software. The analysis indicates that the variation of resonant frequency, Amplitude of the acoustic wave depends on the properties of working gas(es).